2012
DOI: 10.1021/es303152m
|View full text |Cite
|
Sign up to set email alerts
|

Polyfluorinated Amides as a Historical PFCA Source by Electrochemical Fluorination of Alkyl Sulfonyl Fluorides

Abstract: Polyfluorinated amides (PFAMs) are a class of compounds produced as byproducts of polyfluorinated sulfonamide synthesis by electrochemical fluorination (ECF). We measured four PFAM derivatives of perfluorooctanoic acid (PFOA) in a wide range of compounds, experimental materials, and commercial products synthesized by ECF. Initial screening was performed using headspace solid phase microextraction gas chromatography mass spectrometry (SPME-GC-MS), and quantification using in-house synthesized standards was acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Recently, polyfluorinated amides have been reported to occur in perfluoroalkane sulfonamido substances as byproducts of ECF synthesis . In the FTICR-MS spectrum of Foam 12, a series of ions was observed corresponding to A , which is an amide version of T , with n = 4, 5, 6, and 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, polyfluorinated amides have been reported to occur in perfluoroalkane sulfonamido substances as byproducts of ECF synthesis . In the FTICR-MS spectrum of Foam 12, a series of ions was observed corresponding to A , which is an amide version of T , with n = 4, 5, 6, and 7.…”
Section: Resultsmentioning
confidence: 99%
“…In ESI+, loss of ethene follows loss of the amine oxide, which is analogous to losses of Recently, polyfluorinated amides have been reported to occur in perfluoroalkane sulfonamido substances as byproducts of ECF synthesis. 50 In the FTICR-MS spectrum of Foam 12, a series of ions was observed corresponding to A, which is an amide version of T, with n = 4, 5, 6, and 7. An ion corresponding to C7 A was observed in the base fraction and the FTICR-MS spectrum of Foam 2.…”
mentioning
confidence: 98%
“…Further, the stable ratio and correlation between PFOS and PFOA during 1979-2007 suggest that their exposure pathways have changed little or done so concomitantly during this period. One hypothesis, which has been proposed to explain the concurrent decrease in serum concentrations of PFOA and PFOS in cross-sectional studies in other countries, states that consumer products made a significant contribution to the total exposure (direct or through degradation of precursors) to these compounds prior to year 2000 (D'eon and Mabury, 2011; Jackson and Mabury, 2012;Olsen et al, 2008;Vestergren and Cousins, 2009). As their production ceased during 2000-2002 human serum concentrations of PFOA and PFOS might be expected to converge as diet-linked environmental pathways would become increasingly important in a post ban situation (Vestergren and Cousins, 2009).…”
Section: Time Trends In Pfas Concentrationsmentioning
confidence: 99%
“…Long chained PFAA (number of carbon atoms [C] ≥ eight for PFCA, and C ≥ six for PFSA) have higher potentials for bioaccumulation than shorter homologues and have been globally detected in organisms. , In addition, uptake and metabolization of precursor compounds has been suggested to be a source of PFAA to organisms. , Historically, large amounts of perfluorooctane sulfonyl fluoride (POSF) has been used as the starting material for the production of the eight-carbon PFSA, perfluorooctanesulfonic acid (PFOS; ) and PFOS precursor compounds including N -alkyl substituted perfluorooctane sulphonamides with eight perfluorinated C (, for simplicity termed preFOS throughout this work), and potential parent compounds: mono-, di-, and trisubstituted phosphate esters of N -ethyl perfluorooctane sulfonamido ethanol (SAmPAPs). PreFOS and SAmPAPs were used in food contact paper and packaging from the 1970s. , Commercial SAmPAP formulations were dominated by the disubstituted SAmPAP (SAmPAP diester; ), and the presence of this compound has been investigated in a few previous studies. ,, PreFOS have a sulfonyl group, the same perfluorinated moiety as PFOS, and have the potential to be degraded to PFOS if the amine group is replaced with a hydroxy group. PFOS was reported to have higher trophic magnification factors (TMF) compared to other long chained PFAA in several studies, and transformation of the large amount of preFOS to PFOS has been suggested to be the main mechanism behind this . Some preFOS are neutral at environmentally relevant pH, which combined with their larger size, makes them less water-soluble compared to the anionic PFOS, , and thus more prone to reside in environmental compartments other than water.…”
Section: Introductionmentioning
confidence: 99%
“…29,31,32 PreFOS have a sulfonyl group, the same perfluorinated moiety as PFOS, and have the potential to be degraded to PFOS if the amine group is replaced with a hydroxy group. PFOS was reported to have higher trophic magnification factors (TMF) compared to other long chained PFAA in several studies, 33−35 and transformation of the large amount of preFOS 36 to PFOS has been suggested to be the main mechanism behind this. 33 Some preFOS are neutral at environmentally relevant pH, which combined with their larger size, makes them less water-soluble compared to the anionic PFOS, 37,38 and thus more prone to reside in environmental compartments other than water.…”
Section: ■ Introductionmentioning
confidence: 99%